Family Communication in Supporting Adolescent Mental Health in the Digital Era - Imawan, Khaerudin; Billa, Putri Aoelia Tsalsa (International Journal of Business, Economics, and Social Development, 2024)
Family communication in building a support system in adolescents is a very important issue because through open and quality communication families can provide emotional, moral, and practical support that is important for adolescents. The purpose of the research is to be more enthusiastic in running a good and successful life, in terms of parental support and the mentality of adolescents in the digitalisation era and the ability of parents to listen actively. Researchers chose a qualitative approach with a descriptive case study approach and supported using the Family Communication Pattern Theory (FCPT) from Koerner and Fitzpatrick (2002). The results of this study suggest that enhancing family bonds is essential for honest communication and constructive action. Good communication also allows adolescents to feel heard, understood, and get appropriate direction from parents or other family members. Families can provide support such as, information support which functions as a source of receiving information directly, for example advice and suggestions, family assessment support can provide direction such as forms of gratitude and recognition, and instrumental support with family contributions in the form of facilities or infrastructure. Therefore, the family as a support system can help prevent adolescent mentality if there is no real family support, attention or affection, then changes in norms become a source of forming self-character such as temperament, unruly, more confident, and some even yell at parents.